Counseling and Harm Reduction Centers for Vulnerable Women to HIV/AIDS in Iran. - N Fahimfar; A Sedaghat; H Hatami; K Kamali; Mm Gooya (Tehran University of Medical Sciences, 2013)
Human immunodeficiency virus (HIV) is a public health challenge facing both developing and developed nations. Although injecting drug use is even the main route of HIV transmission in Iran, sexual route is rising gradually. Vulnerable women have been considered as important bridging population for driving HIV epidemics. To increase the access to vulnerable women, in 2007, 5 pilot centers were established in risky areas to deliver comprehensive services to women who themselves or their spouses are engaged in drug use, risky sexual behavior or have history of imprisonment. Management of Sexually Transmitted Infection, psychological counseling and harm reduction are provided by female staff. The aim of this study was to report the activities conducting in 2008.Registered information was used to assess the demographic characteristic, HIV/ AIDS related risk factors and services delivered to clients.Till March 2008, 442 clients have been admitted. Most of them (36.2%) had 25-34 years old. 14.3% were illiterate and 31% were totally jobless. The most prevalent risk factors were risky sexual behavior (27.1%) and non-injecting drug use (23.2%). Injecting drug use was detected in 11.3% of attendees. Dividing clients according to marital status, risky sexual behavior was the main risk factor in unmarried (40.2%) and divorced (26.9%) but in married and widow ones, non-injecting drug use was the most (25.8% and 36.5% respectively). Harm reduction (40.5%) and counseling (36.6%) were the most delivered services.Since vulnerable women play a critical role to spread HIV-epidemic to general population, increasing centers provide more access to this population.